HIV co-receptor tropism prediction remains stable over time in treatment-naïve patients. (June 2016) - Philip, Keir EJ; Macartney, Malcolm J; Conibear, Tim CR; Smith, Colette J; Marshall, Neal; Johnson, Margaret A; Haque, Tanzina; Webster, Daniel P
HIV co-receptor tropism determination is essential before prescribing the CCR5 antagonist maraviroc. British HIV Association guidelines suggest tropism testing may remain valid for only 90 days in antiretroviral-naïve patients. We aimed to determine the accuracy of this figure. Tropism was assessed in 26 antiretroviral-naïve patients with ongoing viral replication, sampled yearly from first clinic visit. The V3 region of HIV-1 was sequenced in triplicate, then tropism predicted using the Geno2Pheno system. Baseline tropism prediction remained valid for a median of 52 months (range 7–81). For 19/26 individuals baseline tropism remained unchanged throughout a median of 54 months follow-up; 18 R5 tropic and 1 X4 tropic. In seven patients (27%) baseline tropism switched at least once (range 1–4 switches) during follow-up; however, their baseline tropism prediction remained valid for a median of 45 months. Co-receptor tropism in treatment-naïve patients with ongoing viral replication appears highly stable over time, suggesting that baseline genotypic tropism prediction may be valid for a longer duration in patients delaying ART initiation. In this study, baseline tropism prediction remained valid for a median of 52 months, suggesting current guidelines recommending repeat testing after 90 days may be excessively conservative in their assessment of tropism stability.